Improving Concept Understanding Ability Using Think Talk Write Learning Model in Mathematics Lessons at SD Negeri 42 Banda Aceh - Suryati, Indah; Asri, Khairul (International Conference on Multidisciplinary Research, 2021)
Elementary school is the main foundation in developing an understanding of mathematical concepts. If the basic understanding of students' concepts is not good or weak, then students can’t solve math problems. Therefore, understanding the concept is important to help students in learning mathematics. In the learning process the teacher doesn’t optimize the methods, strategies or learning models. So far, the learning process is only focus by explanations or examples of questions, as a result, when students are faced with different questions, students have difficulty solving problems. This happens because the lack of students' conceptual understanding skills. The purpose of this study was to determine the increase in the ability to understand mathematical concepts through the Think Talk Write learning model. This study uses a quantitative approach, while the design used in this study is the Pre Experiment One group pretest and posttest design. The populations in the study were all students at SD Negeri 42 Banda Aceh, totaling 50 students. The sample in this study was the V grade students as the experimental class, while the grade as the control class. Based on the analysis of research data, it is stated that the value of sig. (2-tailed) the N-Gain score is 0.000 less than 0.05 so Ho is rejected and Ha is accepted. Keywords: Concept Understanding Ability; Mathematics Lesson; TTW.